THE EFFECT OF MARKETING MIX ON THE PURCHASE DECISION OF LIGHTING PRODUCTS AT PT. KINGLED INDONESIA - Heppy Yusus Hulu; Januardin Januardin; Dustin Alvin; Wati Lase; Vinora Vinora (SEAN Institute, 2023)
The results show that the adjusted R Square value is 0.513 which means that 51.3% of Purchasing Decisions demand is jointly influenced by the variables described in the model. while the rest is influenced by factors outside the model. Partially, Product Quality variable has a positive and significant effect, Promotion variable has a positive and significant effect, Price variable has a positive and significant effect, Distribution Channels variable has a positive and significant effect. Simultaneous, Product Quality, Promotion, Price and Distribution Channels, have a positive and significant effect.